1997
DOI: 10.1177/1071181397041001120
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of Responsibility for Product Safety: Warning and Severity of Injury Effects

Abstract: A study explored how injury severity and the presence of warnings influence people's allocation of responsibility for safety during consumer product use. Eighty-eight subjects were shown ten scenarios, one for each of ten products, describing an accident and injury. The subjects assigned responsibility to the manufacturer, the retailer and the consumer (user). Two variables were manipulated: injury severity and the presence or absence of a warning. The mean responsibility assigned to consumers was 85% and 41% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…The results of this study confirm the results of Laughery et al (1997) concerning the strong effect the presence or absence of a warning has on how people allocate responsibility for accidents with consumer products. When a warning is present on a product responsibility for safe conduct shifts towards the consumer.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results of this study confirm the results of Laughery et al (1997) concerning the strong effect the presence or absence of a warning has on how people allocate responsibility for accidents with consumer products. When a warning is present on a product responsibility for safe conduct shifts towards the consumer.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, when warnings are present on a product, the consumer should be allocated a greater percentage of the responsibility for safety behavior relative to the manufacturer as compared to a situation involving a product without warnings. Indeed, this is exactly what Laughery et al (1997) found. However, when the hazard associated with the product was already obvious, warnings did not have nearly the impact on the allocation scheme as when the hazard was not obvious.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…That is, if people assign blame to an entity outside themselves, it may allow them license to behave in a more careless fashion than they would if responsibility for their safety was to lie solely with them. For example, if a manufacturer assumes consumers will be responsible for their own safety, then they may fail to incorporate safety concerns into product design (Laughery, Laughery, McQuilkin, & Lovvoll, 1997;Kalsher, Phoenix, Wogalter, & Braun 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have explored the effects of various factors on the allocation of responsibility for consumer product accidents and injuries. Included in the factors that have been explored are product warnings (Laughery, Laughery, Lovvoll and McQuilkin, 1998), injury severity (Laughery, Laughery, McQuilkin and Lovvoll, 1997), risk taking (Meingast, Laughery, Laughery and Lovvoll, 1999), manufacturer's safety reputation (Kalsher, Wogalter and Williams, 1999;Resnick, Tschen and Kalsher, 1999) and expert testimony (Wogalter, Brantley, Laughery and Lovvoll, 1998). These stndies have implications for understanding jury decision making in product liability litigation.…”
Section: Introductionmentioning
confidence: 99%